Transiting exoplanets from the CoRoT space mission: VII. The "hot-Jupiter"-type planet CoRoT-5b - Rauer, H; Queloz, D; Csizmadia, S; Deleuil, M; Alonso, R; Aigrain, S; Almenara, J; Auvergne, M; Baglin, A; Barge, P; Borde, P; Bouchy, F; et al. (2009)
Aims. The CoRoT space mission continues to photometrically monitor about 12 000 stars in its field-of-view for a series of target fields to search for transiting extrasolar planets ever since 2007. Deep transit signals can be detected quickly in the "alarm-mode" in parallel to the ongoing target field monitoring. CoRoT's first planets have been detected in this mode. Methods. The CoRoT raw lightcurves are filtered for orbital residuals, outliers, and low-frequency stellar signals. The phase folded lightcurve is used to fit the transit signal and derive the main planetary parameters. Radial velocity follow-up observations were initiated to secure the detection and to derive the planet mass. Results. We report the detection of CoRoT-5b, detected during observations of the LRa01 field, the first long-duration field in the galactic anticenter direction. CoRoT-5b is a "hot Jupiter-type" planet with a radius of 1.388(+0.046, -0.047) R_Jup, a mass of 0.467(+0.047, -0.024) M_Jup, and therefore, a mean density of 0.217(+0.031, -0.025) g cm-3. The planet orbits an F9V star of 14.0 mag in 4.0378962 +/- 0.0000019 days at an orbital distance of 0.04947(+0.00026, -0.00029) AU.